PENGARUH KOMBINASI DOSIS PUPUK NITROGEN DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEMBANG KOL (Brassica oleraceae Var botrytis L) sub var cauliflora kultivar PM 126 F1 DI DATARAN RENDAH PADA MUSIM KEMARAU - Rahayu, Yayu Sri; Nurlenawati, Netti; Fitriyah, Endah (Majalah Ilmiah SOLUSI, 2013)
The experiment aims to obtain a combination dose of nitrogen fertilizer and cow manure that can substitute the dosage recommendation and give the best results in the growth and cauliflower plants (Brassica oleraceae var Botrytis L. sub var cauliflora) cultivars PM 126 F1 during the dry season in lowland. The experiment was conducted in the Sirnabaya Village, Eastern Telukjambe subdistrict, Karawang district with altitude of 20 meters above sea level, from July to September 2011. Experimental design used was Randomized Block Design with nine treatments, three replications. The treatments were: 1) A is the dosage recommendations (5000 kg / ha of cow manure + 220 kg / ha urea + 470 kg/ha ZA + 311 kg / ha SP36 + 225 kg / ha KCl), 2) B (5000 kg / ha of cow manure + 439.31 kg / ha urea + 311 kg / ha SP36 + 225 kg / ha KCl), 3) C (5000 kg / ha of cow manure + 220 kg / ha urea + 470 kg of ZA without SP36 without KCl), 4) D (3750 kg / ha of cow manure + 439.31 kg / ha urea + 311 kg / ha SP36 + 225 kg / ha KCl), 5) E (6250 kg / ha of cow manure + 329.5 kg / ha urea + 311 kg / ha SP36 + 225 kg / ha KCl), 6) F (3750 kg / ha of cow manure + 549.14 kg / ha urea + 311 kg / ha + 225 kg SP36 / ha KCl), 7) G (6250 kg / ha of cow manure + 439.31 kg / ha Urea +311 kg / ha SP36 + 225 kg / ha KCl), 8) H (5000 kg / ha of manure cow +329.5 kg / ha Urea +311 kg / ha SP36 + 225 kg / ha KCl), and 9) I (5000 kg / ha of cow manure + 549.14 kg / ha urea + 311 kg / ha + SP36 225 kg / ha KCl). The results showed that treatment of A (dosage recommendation) gives the highest fresh weight of crops, which is 0.63 kg per plant, but not significantly different from other treatments. This shows that in dry environmental conditions, all treatments could substitute dosage recommendations. Keywords: cauliflower plants, nitrogen, cow manure.